Precarity and Flexibility in Platformised Tourism Work: A Scoping Review - Muhammad Fadhli Ramadhan; Tiffany Chairunnisa Ramadhania (Integrasi Sains Media, 2025)
The rapid proliferation of digital labour platforms has fundamentally restructured the global tourism and hospitality labor markets, ushering in a phenomenon widely termed the